Penyuluhan Dan Pendampingan Digital Marketing Pada Usaha Mikro Kecil Dan Menengah (UMKM) Prima Mochi Yogyakarta Melalui Pendekatan Tri N (Niteni, Niroke, Dan Nambahi) - Alfiyansah Ramadhan; Rayi Gustu Mauren; David D Loba; Roberto Ardiawan Duri; Nala Tri Kusuma (LP3M Universitas Putra Bangsa, 2024)
The purpose of this abdimas activity is to introduce and optimise digital platforms used in business activities so that partners are able to expand market reach and increase sales. This abdimas activity was carried out at Prima Mochi Small and Medium Enterprises (MSMEs) which started their business in 2020, the challenges faced by Prima Mochi SMEs are that the business activities carried out are still traditionally based, especially the marketing strategy activities carried out. The method used by the abdimas party in this activity is the Participatory Learning and Action (PLA) method, which is adjusted to the conditions of the abdimas participants. The abdimas team chose this method because the PLA method is based on direct training practices related to digital marketing activities for business ventures carried out. The results of this abdimas activity are that partners are able to take advantage of technology by implementing digital marketing with social media, and building a market place so that partners are able to compete with other competitors who sell similar products, facilitate communication between sellers and buyers, and expand market share. The expected implications of this activity are that abdimas partners are increasingly interested in directly implementing digital marketing strategies, increasing innovation in business ventures and products offered by consumers have positioning compared to other competitors.